2022
DOI: 10.7759/cureus.29925
|View full text |Cite
|
Sign up to set email alerts
|

A Study Linking Axial Length, Corneal Curvature, and Eye Axis With Demographic Characteristics in the Emmetropic Eyes of Bangladeshi People

Abstract: BackgroundAxial length (AL) and corneal curvature (CC) are one of the furthest critical parameters for optometry and oculoplastic surgery. These two variables are crucial in biometry for accurately measuring the power of the intraocular lens in cataract surgery. This research aimed to determine the association linking axial length and corneal curvature with demographic characteristics in emmetropic eyes of Bangladeshi people. MethodsThis descriptive cross-sectional research was carried out among 200 emmetropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…A study on corneal biomechanics among 200 emmetropic Bangladeshi individuals aged 21 to 30 years demonstrated a negative correlation between AL and mean keratometry. [42] Recent studies suggested that cornea can compensate for the impact of AL growth on myopia progression through changes in mean keratometry within a certain range of AL growth. [43][44][45] However, this corneal compensation disappeared when AL > 28 mm.…”
Section: Discussionmentioning
confidence: 99%
“…A study on corneal biomechanics among 200 emmetropic Bangladeshi individuals aged 21 to 30 years demonstrated a negative correlation between AL and mean keratometry. [42] Recent studies suggested that cornea can compensate for the impact of AL growth on myopia progression through changes in mean keratometry within a certain range of AL growth. [43][44][45] However, this corneal compensation disappeared when AL > 28 mm.…”
Section: Discussionmentioning
confidence: 99%
“…This was primarily due to this stage being a critical period for eye development, where various components of the eye were undergoing rapid growth and development, including the gradual increase in AL. Studies have indicated a negative correlation between AL and K [ 28 ]. In the progression of myopia within a certain range of AL growth, the cornea can compensate for the effects of AL growth on myopia through changes in curvature, preventing further progression of myopia [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research [11,24,25] has explored the negative correlation between corneal curvature and AL in the progression of myopia within an AL range of <28mm. This suggests that the cornea compensates for AL growth through changes in its curvature, serving as a physiological adaptation for achieving optimal focusing.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a large multicenter study involving 14,127 children and adolescents aged 4-18 in China revealed that AL shows rapid growth trends between 4-9 years, slows down after age 9, and stabilizes around age 15. Therefore, for myopic children, if myopia is not controlled, AL can continue to grow abnormally during this period, exacerbating the imbalance in dynamic matching and leading to HM [10].Previous studies [11,12] have indicated correlations between AL and anterior segment biometry, although some parameter results have been contradictory due to limitations in technology and equipment. The characteristics and variations in AL and anterior segment biometry in cases of high axial myopia have yet to be clari ed.…”
Section: Introductionmentioning
confidence: 99%